PENGGUNAAN KITAB “KALIMAT AL AF’AL AL YAUMIYAH” DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB - Mohamad Shabirin Shaddiq (Nusantara Hasana Journal, 2025)
This study aims to examine the effectiveness of using the Kalimat Al-Af’al Al-Yaumiyah book in teaching Arabic vocabulary and to identify the challenges encountered during its implementation. The book, authored by Abuya Al-Habib Hasan bin Ahmad Baharun, contains 540 vocabulary items focused on daily action verbs, systematically arranged in past tense (fi'il madhi), present tense (fi'il mudhari’), and infinitive (masdar) forms, and equipped with contextual usage examples. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through direct classroom observation and documentation of learning activities. The results show that the use of the Kalimat Al-Af’al Al-Yaumiyah book is effective in improving students' vocabulary mastery due to its contextual, easy-to-memorize, and practically applicable content. The learning process is conducted in three stages: the initial stage (introduction and material review), the core stage (pronunciation practice, writing, meaning comprehension, and sentence construction), and the final stage (evaluation and memorization tasks). However, several obstacles were identified, both internal (lack of motivation, laziness, psychological factors) and external (learning environment, monotonous methods, limited facilities). The researcher proposes solutions such as engaging teaching methods, interactive learning strategies, special attention to less active students, and providing motivation and rewards to enhance learning enthusiasm. In conclusion, the Kalimat Al-Af’al Al-Yaumiyah book is considered an effective and practical medium for teaching Arabic vocabulary and can be widely implemented in various educational institutions with the support of appropriate teaching methods and strategies.